Beyond the prompt: The Role of User Behavior in Shaping AI-misalignment and Societal Knowledge - Morraya Benhammou (Technology and Regulation, 2025)
This research paper explores the concept of AI-misalignment, differentiating between perspectives of AI model designers and users. It delves into the notion of user-centric AI misalignment, breaking it down into three categories: user responsibility, user intent, and user influence. The focus is on how users influence misalignment in both the large models and the outputs generated through AI. The research examines how user behavior may inadvertently contribute to the spread of disinformation through AI-generated hallucinations, or deliberately use AI to propagate misinformation for propaganda purposes. Additionally, it discusses the concept of user accountability as part of this behavior, highlighting that from a user’s perspective, the only controllable aspect is their acceptance through ignorance. Furthermore, it explores how user behavior can shape AI models through reinforcement learning from human feedback (RLHF) and how they can influence the models through model collapse. This kind of misalignment can significantly affect knowledge integrity, possibly resulting in knowledge erosion.